Combining Pharmacological Countermeasures to Attenuate the Acute Radiation Syndrome-A Concise Review - Hofer, Michal; Hoferová, Zuzana; Depeš, Daniel; Falk, Martin (Molecules, 2017)
The goal of combined pharmacological approaches in the treatment of the acute radiation syndrome (ARS) is to obtain an effective therapy producing a minimum of undesirable side effects. This review summarizes important data from studies evaluating the efficacy of combining radioprotective agents developed for administration prior to irradiation and therapeutic agents administered in a post-irradiation treatment regimen. Many of the evaluated results show additivity, or even synergism, of the combined treatments in comparison with the effects of the individual component administrations. It can be deduced from these findings that the research in which combined treatments with radioprotectors/radiomitigators are explored, tested, and evaluated is well-founded. The requirement for studies highly emphasizing the need to minimize undesirable side effects of the radioprotective/radiomitigating therapies is stressed.
Keywords: rozvrh dávkování léků; Animals; amifostin; metformin; fixní kombinace léků; Amifostine; vitamin E; Dinoprostone; Radiation Injuries, Experimental; Vitamin E; lidé; dinoproston; Drug Administration Schedule; akutní radiační syndrom; Misoprostol; Metformin; Acute Radiation Syndrome; faktor stimulující kolonie granulocytů; misoprostol; Granulocyte Colony-Stimulating Factor; experimentální radiační poranění; Drug Synergism; Radiation-Protective Agents; synergismus léků; zvířata; Drug Combinations; radioprotektivní látky; Humans